A Study Of KM Process And KM Enabler In A Malaysian Community College - Yusoff, Mohamad Yusrizal Mohamed; Mahmood, Ahmad Kamil; Jaafar, Jafreezal (Journal of Knowledge Management Practice, 2012)
This aim of this study is to discover the relationship of KM implementation and KM enabler among members in community college. It also shows relationship between demography of respondents with KM enablers in community colleges. The research hypotheses were examined while considering KM enabler (leadership, culture, process, explicit, tacit, hub, market, measure, skill and infrastructure) based on demographic variables (academic qualification, gender and job designation). This study was conducted using the correlation method. The statistical population consisted of 21 college members in Pasir Salak Community College (KKPS) from January till October 2011. Survey question was developed based on previous research which consists of 10 questions of KM was distributed via online. We received 21 completed questionnaires. The results indicate that there is no significant relationship between KM implementation and enablers. In addition, there is a certain enabler have a significant difference between KM enabler and college members considering the variables of academic qualification, gender, and job designation.
Keywords: knowledge management; Community college; Knowledge transfer; Lifelong learning; Local community